GLOBAL CHANGES AND SHOOTING PERIOD CHARACTERISTICS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The article reflects the global changes observed on the planet Earth, and the features of the transition period.